Poverty in the Context Violence in Noviolet Bulawayo’s We Need New Names and Petina Gappah’s An Elegy of Easterly - Kehinde, Kemi Rebecca (NIU Journal of Humanities, 2021)
This study is a critical examination of the depictions of poverty in the context of violence in We Need New Names (2013) by NoViolet Bulawayo and Petina Gappahâ€™s An Elegy Of Easterly (2009).  The paper is focused on the literary representations of poverty and the way in which the writers attempt in their depictions to give the voiceless a voice through narrative devices, thereby allowing the characters to claim agency and speak over the narrative of poverty in the context of violence in Zimbabwe. It is no news that the last decade in Zimbabwe was characterised by an unprecedented economic and political crisis. It is for this reason this study explores how the writers acknowledge poverty both culturally and aesthetically while at the same time emphasizing that violence and indigence is materially and socially real. In addition, the research deploys the desk research method to analyse the texts while paying specific attention to the socio-cultural and economic contexts within which the cultural production takes place. This involves an in-depth reading and study of both primary and secondary materials for the critical evaluation of the texts. The concept of Structural violence will be used for the analysis of the texts in order to examine the depiction of poverty in Zimbabwe as reflected in the selected texts, as well as investigate the portrayal of political violence after independence in the selected Zimbabwean texts. The study concludes that literature provides an exceptional prospect by highlighting on individual experiences of indigence as it accommodates the diversity of voices that express and voice these experiences. In other words, this study establishes that literary depictions of violence and poverty can be a source of authoritative knowledge on poverty, since they provide wide-ranging and focused descriptions of lived experiences of poverty Keywords : Poverty, violence, Zimbabwe, crisis, women writers